Modern Post - Arundale, Scott; Trieu, Tashi (Routledge, 2014)
With the shift from film to digital, today's filmmakers are empowered by an arsenal of powerful, creative options with which to tell their story. Modern Post examines and demystifies these tools and workflows and demonstrates how these decisions can empower your storytelling. Using non-technical language, authors Scott Arundale and Tashi Trieu guide you through everything you should consider before you start shooting. They begin with a look to past methodologies starting with traditional film techniques and how they impact current trends. Next they offer a look at the latest generation of digital camera and capture systems. The authors move on to cover: * Preproduction- what camera is best for telling your story and why, budgeting for post * Production- on-set data management, dailies, green screen, digital cinematography * Postproduction- RAW vs. compressed footage, editing, visual effects, color correction, sound and deliverables including DCP creation The book features cutting-edge discussion about the role of the digital imaging technician (DIT), how you can best use the Cloud, motion graphics, sound design, and much more. Case studies show you these solutions being applied in real-world situations, and the companion website features videos of techniques discussed in the book, as well as timely updates about technological changes in the landscape. www.focalpress.com/cw/arundale.